ANALISIS PENGARUH EXPERIENTIAL MARKETING DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN UNTUK MENDORONG MINAT BELI ULANG (Studi pada Member Sanggar Senam Kharisma Semarang) - Alfa Lionora, Clarisa; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2015)
This study was conducted at a gymnasium that called Kharisma, which is located in Banyumanik, Semarang. Existing data on the gymnasium Kharisma shows a decreasing number of members in 2013-1014. This study aims to determine whether experiential marketing and service quality on customer satisfaction influece repurchase intention.The sample used in this research is a 150 member of gymnasium Kharisma. Data analysis methods used in this study is quantitative method and analyzed using multiple linear regressions.The results of the research shows that experiential marketing and service quality have a positive impact to customer satisfaction with the regression coefficient Y1= 0,659X1 + 0,201X2. While customer satisfaction is also has a positive impact to repurchase intention on the value of the regression coefficient Y2 = 0,957Y1